Clinical Analysis of Childhood Acute Lymphoblastic Leukemia With Epilepsy Seizures - Li, Rui; Tang, Ji-Hong; Zhang, Bing-Bing; Shi, Xiao-Yan; Dai, Yuan-Yuan; Qu, Rui (Frontiers in Neurology, 2022)
Objective In order to analyze the clinical characteristics of epileptic seizures in children with acute lymphoblastic leukemia (ALL) during treatment. Methods The clinical and imaging data of children diagnosed as ALL with epilepsy seizures from January 2013 to December 2020 were retrospectively analyzed. Results A total of 2217 children with ALL were admitted during the study, of whom 229 (10.33%) had epileptic seizures after ALL treatment. Among them, 45 (19.65%) were in the high-risk group and 184 (80.35%) were in the low-risk group. Epileptic seizures mainly occurred in the induction remission period (24.02%), maintenance treatment period (25.33%) and after bone marrow transplantation (21.40%). The common causes were MTX-related demyelinating encephalopathy (34.06%) and reversible posterior encephalopathy syndrome (PRES) (25.3%). The first symptom was mainly convulsion (34.50%). The first attack had a comprehensive attack and partial attack. Most patients stop themselves. 30 cases (13.10%) had acute recurrence of epilepsy (recurrence within 3 months after the first attack), and 49 cases (25.76%) had neurological dysfunction after follow-up. 36 cases developed symptomatic epilepsy. Among the 130 children who completed the follow-up, 78 (60.00%) had no obvious neurological sequelae, and 52 (40.0%) had neurological sequelae. Among the 52 cases, there were 34 cases of mild sequelae and 18 cases of severe sequelae, including 8 cases of epilepsy combined with cognitive impairment. Conclusion Epileptic seizure is a common neurological complication during ALL treatment. The etiology and associated manifestations of the first epileptic seizure are diverse. Early neuroimaging and EEG examination are helpful for early diagnosis and treatment.